The Jesuit China Mission in an Italian Frame - Catto, Michela (Church history and religious culture, 2024)
In recent decades, global history studies devoted specifically to the Society of Jesus have contributed significantly to research on missions and the emergence of the concept of global Christianity. In the absence of a prevailing political and economic role played by the Italian Peninsula in the Early Modern Age, the Papacy acted with its universal body and offshoots consisting of missionaries; through these, Rome projected itself into the spaces of global politics and intellectual discussions. The Papacy and Society of Jesus, both global institutions based in Rome, found themselves at odds in dealing with many of the issues raised by journeys in other continents. These include the controversy of Chinese rites, a question this article addresses once again setting off from Rome and the debates that took place as the Papacy prepared to condemn these rites.